Cancer patterns, trends and projections in Latin America and the Caribbean: a global context - Freddie Bray; Marion Piñeros (Instituto Nacional de Salud Pública, 2016)
Objective. To develop a situation analysis encompassing the patterns and trends in cancer incidence and mortality in South and Central America and the Caribbean, with comparisons globally and with selected external countries. Materials and methods. Data on cancer incidence and mortality rates for 31 countries were obtained from the 2012 GLOBOCAN database. Incidence and mortality trends for selected countries were analysed with data from the Cancer Incidence in Five Continents (CI5) series and the WHO Mortality Database, respectively. Results. In 2012, almost 1.1 million new cancer cases were estimated annually, with important variations in rates across countries. The most common cancer types were breast, prostate, colorectum and lung cancer; stomach and cervical cancer ranked high in less developed countries. Increasing trends were observed in prostate, breast and colorectal cancer; lung cancer mortality trends diverged among males and females, while cervix cancer incidence and stomach cancer mortality uniformly decreased. A 66% increase in cancer cases in the region by 2030 is projected based on population aging and growth. Conclusions. Cancer patterns and trends reflect the significant sociodemographic changes in the region: the growing burden imposes great challenges to national health care systems to implement cancer control actions, while improving cancer surveillance to effectively measure the response. DOI: http://dx.doi.org/10.21149/spm.v58i2.7779